Digitization and sustainability of local collection : an observation of digitization activities among Malaysian universities libraries - Mat, Shaifol Yazam; Mohd Nasir, Aishah (2005)
Malaysian academic libraries have responded well to the government’s IT agenda. They are among the first group of libraries to embark on digitization projects. This paper attempts to discuss the types of materials digitized, guidelines, policies and provision for access to the digitized materials. It also discusses some of the issues and challenges in this process of enriching the local digital content. An appropriate training module with practical guidelines and policy is recommended to ensure continuity and sustainability of these projects.